The Effect of Ethyl Alcohol on Some Sperm Characterstics in Testis and Epididymis of Albino Rats - G. A. Al-Bairuty (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
This study has been carried out on 20 adult rats Ruttus norregicus. Their weights are 350-400 g in order to determine the effect of different concentration of ethyle alcohol 20%.30%.40% on some sperm charactristics of male reproductive system. The rats were divided into 4 groups with 5 animals for each group. The first group was considered as a control while the second group was treated by 5 ml of 20% ethvl alcohol for each animal an so on for other groups according to the concentration mentioned above respectively for 30 days through gastric ways .The results showed that there an average significant was decrease (p<0.05). In the percentage of sperm live and significant decrease (p<0.05) in sperm number while the sperm abnormality was a significantly increase in each of testes and epididymis with tow region head and tail of ethyl alcohol for long periods on some sperm charactristics of male. This study showed the range of effectiveness of consumption reproductive system activity of these animals rats which lead finally in decrasing the sexual